PERBEDAAN TINGKAT KECEMASAN IBU HAMIL PRIMIGRAVIDA DENGAN MULTIGRAVIDA DI ERA PANDEMI COVID-19 DI WILAYAH KABUPATEN KENDAL - Rozikhan Rozikhan; Titik Sapartinah (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
Anxiety that occurs in pregnant women is a serious problem because the mortality rate for pregnant women is 80% due to high anxiety. The emergence of anxiety due to influencing faktors, including internal faktors of pregnancy it self and external faktors due to the family environment and the environment outside the family. In developed countries the level of anxiety is around 7-20% and in developing countries more than 20%. The level of anxiety that occurs in primigravida pregnant women is greater than that of multigravida pregnant women, but in the era of the Covid-19 pandemic it can increase anxiety in pregnant women, especially those who are approaching childbirth process. The Objective of this research is there a difference in the level of anxiety between primary and multi-pregnant women in the era of Covid-19 pandemic.The design of this research uses crosscectional study, where between exposure and outcame is seen at the same time. The sampling method used accidental sampling, obtained a total of 72 respondents, consisting of 21 respondents with primigravida status and 51 respondents with multigravida status. The research analysis used the compare mean of independent sample t-test. The primigravida-pregnant women is more anxiety (57.1%) compared to multi-pregnant women (27.4%). There is a significant difference in the value of anxiety between primary and multi pregnant women in the trimester III in the era Covid-19 pandemic, (p value 0.003 0.05)